INTERPRETATION OF ANDRIĆ'S DISSERTATION THROUGH THE THEORY OF HISTORICAL INSTITUTIONALISM - Nurkic, Benjamin (Glasnik Advokatske komore Vojvodine, 2022)
Andrić's doctoral dissertation entitled "Development of spiritual life in Bosnia under the influence of Turkish rule" has so far initiated many discussions, mostly based on criticism of the methodology used by Andrić in this dissertation, but also, many criticisms related to challenges to scientific the character of the dissertation itself. In this paper, the author focuses on a completely different segment of Andrić 's dissertation, which previous analyzes and critiques of Andrić's s dissertation have not covered. Here we are talking about the problem of corruption in the Ottoman Empire, and certainly about the problem of corruption in Bosnia, as part of the Ottoman Empire. The paper analyzes the scientific basis of Andrić's claims in the dissertation on the ubiquity of corruption in the Ottoman Empire, and the possible impact of corruption on Ottoman institutions on the development of institutions in Bosnia and Herzegovina. The author explains the importance of Andrić 's dissertation for a better understanding of the problem of corruption in the functioning of the institutions of Bosnia and Herzegovina with the theory of historical institutionalism.
Keywords: Ivo Andrić, corruption, Ottoman Empire, historical institutionalism, the rule of law.